Does stock market-based financial development promotes economic growth in emerging markets? New evidence from Nigeria - Nathaniel, Solomon Prince; Omojolaibi, Joseph Ayoola; Ezeh, Chikaodili Josephine (Serbian Journal of Management, 2020)
This study examines the effect of stock market development on economic growth in Nigeria. The study spans the period 1980-2016. It employs the ARDL approach to cointegration. Evidence from the study indicates that stock market development promotes economic growth in the short-run, but in the long-run, the growth impact of stock market development is not significant. The growth impact of market capitalization, value of shares traded, and market turnover ratio are all significant in the short run while that of trade openness is not. Meanwhile, trade openness is the only variable that significantly impacts economic growth in the long-run. The Bounds test for cointegration reveals a long-run relationship among the variables. All the variables, apart from trade openness, are positively correlated with economic growth. The results of this study imply that stock market development plays a major role in economic growth in Nigeria. It is recommended that the regulatory authority enacts policies that will promote liquidity, stability and accountability in the stock market which could possibly perpetuate economic growth in Nigeria.
Keywords: stock market development; economic growth; time series analysis; block exogeneity Wald tests; ARDL